ANALISIS DEIKSIS PERSONA, WAKTU DAN TEMPAT DALAM NOVEL “BIBI GILL” KARYA TERE LIYE DAN KONTRIBUSINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Vera Sriwari Santi Radja; Labu Djuli; Margareta P. E. Djokaho (STKIP Subang, 2026)
This study is titled “Analysis of Personal, Temporal, and Spatial Deixis in Tere Liye’s Novel *Bibi Gill* and Its Contribution to Indonesian Language Learning.” The purpose of this study is to describe and analyze the forms of personal, temporal, and spatial deixis in Tere Liye’s novel *Bibi Gill*, as well as to examine their contribution to Indonesian language learning. This is a qualitative descriptive study using a pragmatic approach. The data in this study consist of words, phrases, or expressions containing deictic elements sourced from the text of Tere Liye’s novel *Bibi Gill*, which were collected using the read-and-record technique. The results of the study show that there were a total of 719 instances of deictic data, divided into three types: 658 instances of personal deictics, 20 instances of temporal deictics, and 41 instances of locative deictics. The most dominant type of deictic found was personal deictics, indicating that this novel is dominated by interactions between characters and a narrative focused on the speakers. The results of this study make a tangible contribution to Indonesian language learning for both teachers and students. For teachers, this study aids in designing lessons, improving the accuracy of language assessment, supporting the development of systematic teaching materials, and identifying students’ language errors. For students, an understanding of deictics helps improve their comprehension of communicative context, linguistic politeness, text comprehension, and confidence in interacting with others.